Co-Operative Stores in New England - Bemis, Edward W. (Quarterly Journal of Economics, 1897)
Co-Operative Stores in New England Get access Edward W. Bemis Edward W. Bemis Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 11, Issue 4, July 1897, Page 449, https://doi.org/10.2307/1880720 Published: 01 July 1897